Characterisation of the new HPGe detectors at INPP/NCSR “Demokritos”... and future (n,2n) reactions to be studied - Peoviti, Maria; Axiotis, Michail; Georgali, Efstathia; Harissopulos, Sotirios; Lagoyannis, Anastasios; Patronis, Nikolaos (HNPS Advances in Nuclear Physics, 2022)
Within the present work the HPGe detectors of the Institute of Nuclear and Particle Physics at NCSR “Demokritos” were fully characterized in terms of their efficiency. The three n-type 80% relative efficiency HPGe were recently acquired in the framework of the CALIBRA project. All detectors are equipped with carbon epoxy windows that allow detection of low energy γ-rays. Beside the efficiency characterization, the three detectors were fully modeled by means of GEANT4. In all cases the simulated detector geometries were fine-tuned so as to fully reproduce the experimental efficiency data at different source-to-detector distances. Finally, as a demonstration of the new offered abilities, the efficiency characterization and the GEANT4 modeling of the three HPGe detectors was used for a feasibility study of possible/future (n,2n) activation measurements on medium-weight nuclei.